Pengaruh Perceived Public Stigma terhadap Sikap Mencari Bantuan Profesional Psikologis pada Mahasiswa - Basmura, Ghinanda Farras; Nio, Suci Rahma (Lembaga Yasin AlSys, 2024)
Students are a group that is vulnerable to experiencing mental health problems. This is because they are in a transition period towards adulthood which is one of the most stressful times in human life. However, not all students are able to face all changes in life so that every human being needs a coping to deal with the problems they experience. One of the best coping to do is to seek professional psychological help. In this study, the influence of perceived public stigma to attitudes towards professional help seeking will be tested. This research method is quantitative with a linear regression research design. The subjects in this study were 115 students of Padang State University who had psychological problems. The research data were analyzed using SPSS 25 with a simple linear regression hypothesis test. The results of this study are that there is a significant influence of perceived public stigma on the attitude of seeking professional psychological help (F = 21.573; sig = 0.000) with an influence of 16% (R Square = 0.16).